Monitoring the impact of COVID-19 in Myanmar: Yangon peri-urban poultry farmers - August 2020 survey round - Fang, Peixun; Belton, Ben; Ei Win, Hnin; Zhang, Xiaobo (International Food Policy Research Institute, 2020)
Poultry farmers in Myanmar were interviewed by telephone in early June, late June, early July, and late July 2020 to determine how their businesses were being affected by COVID-19 related restrictions. The results of those surveys were published in Myanmar Strategy Support Program Policy Notes 11, 13, 19, and 21, respectively. To trace the continuing impact of the COVID-19 pandemic on their economic activities, a fifth phone survey of poultry farmers was done in August 2020. The fifth survey included 228 poultry farmers (163 broiler and 65 layer farms) in the Yangon peri-urban area (Ayeyarwady, Bago, and Yangon regions) who had been interviewed in the first four rounds of the survey. The same survey questionnaire was used. Because this survey round is about two months after the early June survey round, which is the length of a full broiler production cycle, we again asked questions in this round about the last complete broiler production cycle. This Policy Note reports on the results of this fifth survey round.